Burnout and Well-Being Among Medical Professionals in China: A National Cross-Sectional Study - Xiao, Ying; Dong, Dong; Zhang, Huanyu; Chen, Peipei; Li, Xiangyan; Tian, Zhuang; Jing, Zhicheng; Zhang, Shuyang (Frontiers in Public Health, 2022)
Objective To determine the profile of Chinese medical professionals with burnout symptoms at the national level and identify the association between capability well-being and burnout. Design and Setting A cross-sectional study in a nonrandom national sample of medical staff from 6 provinces across western, central and eastern China. Participants Physicians, medical laboratory scientists, nurses, and general practitioners aged 18 years or above who submitted a completed online questionnaire from June 2019 to January 2020 successfully (N = 25,120). Main Outcome Measures The prevalence of burnout symptoms was assessed by the 22-item Maslach Burnout Inventory-Human Services Survey (MBI-HSS), which consists of three domains: emotional exhaustion (EE), depersonalization (DP), and personal achievement (PA). The overall high burnout was defined as EE score ≥27 or DP score ≥10. The capability well-being was measured by the Investigating Choice Experiments Capability Measure for Adults (ICECAP-A) and the overall ICECAP-A score was calculated using the UK value set, ranging from a score of 0–1. Multivariable logistic regression analysis was used to identify the association between well-being and the overall high burnout. Results Among the 25,120 participants, 60.8% of the participants reported at least one symptom of burnout, whereas 11.2% reported all three symptoms of burnout. In the adjusted model, ICECAP-A score was independently associated with high burnout (AOR = 0.018, 95% CI = 0.015–0.022). Medical staff who were males, with shorter working years, working in tertiary hospitals, and those with the specialties of psychiatry, intensive care, emergency medicine, internal medicine, oncology, and pediatrics were at higher risk of reporting burnout symptoms. Conclusion The burnout symptoms were relatively common among Chinese medical staff and they were found to be independently associated with capability well-being in health professionals. Interventions should be enhanced on vulnerable groups to reduce burnout and promote well-being in future studies.